Autistic Shame: Reflections on an Underrecognized Determinant of Autistic Mental Health - Mary Doherty (Autism in Adulthood, 2026)
Shame is a deeply painful emotion that is underexplored in autism research and autistic community spaces. While we commonly discuss stigma, we rarely examine how it is embodied and experienced as shame. This perspective piece argues that shame is a critical, yet largely unrecognized, determinant of autistic mental health outcomes, operating as a hidden link between societal stigma and the elevated rates of depression, anxiety, self-harm, and suicidality among autistic adults. Drawing on research with autistic psychiatrists and personal experience as an autistic clinician–researcher, I trace how shame became visible as the overarching theme in my doctoral research – so pervasive it was initially invisible. The recognition of autistic shame has proven challenging to disseminate, with resistance to these findings illustrating the very dynamics being studied: when research exposes uncomfortable truths about shame, defensive responses often follow patterns described in Nathanson’s Compass of Shame. Autistic shame is the internalized sense of defectiveness tied specifically to one’s autistic identity and traits. It is externally imposed through lifelong exposure to neuronormative expectations where difference is misinterpreted as deficit. It manifests in multiple contexts: Reciprocally shaming social interactions, health care settings where autistic patients are dismissed and disbelieved, and community conflicts where heterogeneity is weaponized to silence advocacy. For autistic people, alexithymia can make shame difficult to recognize, though clues such as the desire to withdraw and experiences of rage may signal its presence. Addressing autistic shame requires explicit therapeutic attention, self-compassion practices adapted for autistic cognition, and neurodiversity-affirmative approaches that reframe difference rather than deficit. Understanding shame offers tangible pathways toward improved mental health and authentic autistic flourishing.